PDRB Hijau dalam Perkembangan Wilayah di Kota Depok - Setyo Nugroho; Kukuh Murtilaksono; Seokmana Soma (TATALOKA, 2020)
Depok City has become one of the cities with high economic growth in West Java Province. This high growth, however, also has impact on the environment. This study aimed to review the level of regional development and linkages among economic sectors and calculate Green GRDP for regional development directions. Scalogram method and input output analysis were applied to indicate the level of regional development and identify the key sectors. The value of green GRDP was obtained from the calculation of natural resource depletion and calculation of environmental degradation. The research showed that 65.08% of villages in Depok City were in the form of hinterland. The sector of electricity, gas, and drinking water was the key  sector of economic development in Depok City. Furthermore, the Green GRDP value only had a difference of 4.47% or Rp2,610.78 billion, compared to Brown GRDP. However, if the GRDP difference was compared to the original local government revenue, this would consume all of the income. The analysis resulted green GRDP was more relevant to be applied as an economic indicator because better description the level of overall welfare.